2019
DOI: 10.1155/2019/2614060
|View full text |Cite
|
Sign up to set email alerts
|

Development and Preliminary Investigation of a Semiautonomous Socially Assistive Robot (SAR) Designed to Elicit Communication, Motor Skills, Emotion, and Visual Regard (Engagement) from Young Children with Complex Cerebral Palsy: A Pilot Comparative Trial

Abstract: Through play, typically developing children manipulate objects and interact with peers to establish and develop physical, cognitive, language, and social skills. However, children with complex disabilities and/or developmental delays have limited play experiences, thus compromising the quality of play and acquisition of skills. Assistive technologies have been developed to increase opportunities and level of interaction for children with disabilities to facilitate learning and development. One type of technolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
(34 reference statements)
0
4
0
Order By: Relevance
“…Although our results were similar, we found that in addition to low sensory threshold, avoidance, and sensitivity behavior, sensory seeking response also improved in children with CP with CVI. It is known that children with CP with CVI and children with CP without CVI due to neural involvement have lower sensory, motor, and cognitive skills than children with TD, and their functional independence levels are lower accordingly [34,35]. Children with functional disabilities may exhibit sensory seeking because they do not have adequate access to sensory stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Although our results were similar, we found that in addition to low sensory threshold, avoidance, and sensitivity behavior, sensory seeking response also improved in children with CP with CVI. It is known that children with CP with CVI and children with CP without CVI due to neural involvement have lower sensory, motor, and cognitive skills than children with TD, and their functional independence levels are lower accordingly [34,35]. Children with functional disabilities may exhibit sensory seeking because they do not have adequate access to sensory stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Two children (P13 and P14) drew a robot interacting with a child, with their drawings showing clear differences between the appearance of the robot and that of the child. Children with cerebral palsy have shown playfulness and engagement in play activities facilitated by several animal-like and machine-like robotic toys (Air Swimmer, Cubelets, Dash and Dot, Edison and Zoomer) [9], a socially assistive robot [11], ZORA (a version of the NAO robot with software developed for the field of care) [30], and an adapted car-like Lego robot [7]. To date, no studies have compared the acceptance of robots with different appearances (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Robots' characteristics and styles of interaction influence the levels of engagement and enjoyment children expect to find when interacting with robots, which is critical for the formation of child-robot interaction. A considerable amount of research has been dedicated to developing social robots that are able to recognize and react to human emotions using artificial intelligence [6,11]. Thus, this feature is being sought by developers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is a group of people with disabilities in lower and/or upper limbs, or with severe motor dysfunctions who cannot manipulate conventional mechanical devices [ 1 , 2 , 4 ]. This group of people require permanent assistance, i.e., they depend on a third person to manipulate the device, get out of bed, use the toilet; in short, to carry out any type of daily activity, thus generating dependence on their family, friends or caregivers [ 5 ].…”
Section: Introductionmentioning
confidence: 99%